A VIEW TO THE GENERAL CHARACTERISTICS OF THE ALEPPO MADRASAS IN MAMLUKS PERIOD - Esra ATMACA (Fırat University, 2019)
Aleppo was important science center following Capital Cairo and Damascus in Mamluk Period before Ottoman. Operating the vast majority of scientific center inherited from Zengis and Ayyubis and these madrasas were often built by statemen. But sometimes scientist have built a madrasa. Before the Mamluk Period, many madrasas built by Nureddin Mahmud Zengi and Ayyubi Statemen. Some of them are given to the use of Muslims while previously belonging to other religions, these structures or those created converted the mosque madrasa and some of them were built as a private. Madrasas were named with the name of the founder and the needs of madrasas had been supplying thanks to foundation established by the founder. The majority of the foundation property was property income. This income was spent for both stationary and additional expenses. In the vast majority of these madrasas was trained law of Hanefî or Şâfiî, or both Hanefî and Şâfiî. There were very few madrasas in which were trained law of Mâlikî and Hanbelî. It were trained its law, law of other denominations and other branches of science in the general madrasas that taught Islamic law. Conditions were determined about education and administration of madrasas. It was required textbooks and names will be mentioned in prayer in these conditions. There were other specialized institutions outside the general madrasas in life sciences of Aleppo. They were darulquran, darulhadith and bimaristan.